Tunneling spectra of break junctions involving Nb3Sn: III Международный семинар по микроконтактной спектроскопии Харьков, Украина, 8–11 сентября 2014 г. - Ekino, Toshikazu; Sugimoto, Akira; Sakai, Yuta; Gabovich, Alexander M.; Akimitsu, Jun (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The electronic gap structure of Nb3Sn was measured by the break-junction (BJ) tunneling technique. The su-perconducting gap values are estimated to be in the range 2Δ = 4–5.5 meV at T = 4.2 K as follows from the observed distinct conductance peaks. In addition to the superconducting gap structure, we observed reproducible hump-like structures at the biases of about ± 20 and ± 50 mV. Such a coexistence of gap and hump structures resembles the situation found in the high-Tc copper-oxide superconductors. Above the superconducting critical temperature Tc ~ 18 K, the humps appear as the only gap-like structures. Their possible origin is discussed in connection to the structural phase transition occurring in Nb3Sn.